Phenotyping COPD exacerbations using imaging and blood-based biomarkers - Alotaibi NM; Chen V; Hollander Z; Hague CJ; Murphy DT; Leipsic JA; DeMarco ML; FitzGerald JM; McManus BM; Ng RT; Sin DD (International Journal of COPD, 2018)
Nawaf M Alotaibi,1,2 Virginia Chen,1,3,4 Zsuzsanna Hollander,1,3,4 Cameron J Hague,5 Darra T Murphy,5 Jonathon A Leipsic,5 Mari L DeMarco,1,6 J Mark FitzGerald,7,8 Bruce M McManus,1,3,4,6 Raymond T Ng,4,9 Don D Sin1,3,7 1Centre for Heart Lung Innovation, James Hogg Research Centre, St Paul’s Hospital, Vancouver, BC, Canada; 2Division of Pulmonary Medicine, Department of Medicine, College of Medicine, King Saud University, Riyadh, Saudi Arabia; 3Institute for Heart Lung Health, 4PROOF Centre of Excellence, 5Department of Radiology, St Paul’s Hospital, 6Department of Pathology and Laboratory Medicine, 7Division of Respiratory Medicine, Department of Medicine, University of British Columbia, 8The Lung Centre, Vancouver General Hospital, 9Department of Computer Sciences, University of British Columbia, Vancouver, BC, Canada Rationale: Acute exacerbations of chronic obstructive pulmonary disease (AECOPD) are caused by a variety of different etiologic agents. Our aim was to phenotype COPD exacerbations using imaging (chest X-ray [CXR] and computed tomography [CT]) and to determine the possible role of the blood tests (C-reactive protein [CRP], the N-terminal prohormone brain natriuretic peptide [NT-proBNP]) as diagnostic biomarkers. Materials and methods: Subjects who were hospitalized with a primary diagnosis of AECOPD and who had had CXRs, CT scans, and blood collection for CRP and NT-proBNP were assessed in this study. Radiologist blinded to the clinical and laboratory characteristics of the subjects interpreted their CXRs and CT images. ANOVA and Spearman’s correlation were performed to test for associations between these imaging parameters and the blood-based biomarkers NT-proBNP and CRP; logistic regression models were used to assess the performance of these biomarkers in predicting the radiological parameters. Results: A total of 309 subjects were examined for this study. Subjects had a mean age of 65.6±11.1 years, 66.7% of them were males, and 62.4% were current smokers, with a mean FEV1 54.4%±21.5% of predicted. Blood NT-proBNP concentrations were associated with cardiac enlargement (area under the curve [AUC] =0.72, P<0.001), pulmonary edema (AUC =0.63, P=0.009), and pleural effusion on CXR (AUC =0.64, P=0.01); whereas on CT images, NT-proBNP concentrations were associated with pleural effusion (AUC =0.71, P=0.002). Serum CRP concentrations, on the other hand, were associated with consolidation on CT images (AUC =0.75, P<0.001), ground glass opacities (AUC =0.64, P=0.028), and pleural effusion (AUC =0.72, P<0.001) on CT images. A serum CRP sensitivity-oriented cutoff point of 11.5 mg/L was selected for the presence of consolidation on CT images in subjects admitted as cases of AECOPD, which has a sensitivity of 91% and a specificity of 53% (P<0.001). Conclusion: Elevated CRP may indicate the presence of pneumonia, while elevated NT-proBNP may indicate cardiac dysfunction. These readily available blood-based biomarkers may provide more accurate phenotyping of AECOPD and enable the discovery of more precise therapies. Keywords: chronic obstructive pulmonary disease, exacerbation, biomarker, CT scan, chest X-ray